Study on Curing Process and Properties of UV Curable Polyurethane Acrylate Adhesive - Zhang, Xixiang; Wang, Ming; Zhong, Anyong; Chen, Deben (Asian Journal of Chemistry, 2012)
We synthesize a novel UV curable polyurethane acrylate adhesive which can be used in the application of liquid crystal display panel and organic light emitting diode panel. Fourier transform infrared spectroscopy is used to investigate the effects of the curing time, photoinitiator types and their contents,reactive diluent types on the curing behaviour. The electrical and mechanical properties and the water resistivity of the UV-curable adhesive are investigated in this study.